1991
DOI: 10.1093/oxfordjournals.jhered.a111105
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolution of Genome Size of Birds

Abstract: We measured genome size (nuclear DNA content) by fluorescence flow cytometry in 55 species of birds representing 12 different orders. Similar studies were performed in approximately 100 species by laboratories using absorption cytophotometry of Feulgen-stained nuclei. Although there have been apparent discrepancies in the assigned values for the species used as a reference, the values obtained in the different laboratories are generally in agreement. When the data are standardized in relation to a diploid (2C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 25 publications
7
107
1
Order By: Relevance
“…The question of whether the small genomes of birds are ancestral or derived ( Tiersch & Wachtel 1991)-that is, 'whether they have jettisoned their genomic baggage or whether it was never loaded in the first place' (Gregory 2002a,b)-is central to determining whether small genomes represent an adaptation to flight per se. New light has been recently shed on this issue by Organ et al (2007) who analysed the sizes of fossil osteocytes in dinosaurs and concluded that birds inherited already diminutive genomes from ancestral theropod dinosaurs (see also Ellegren 2007;Zimmer 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question of whether the small genomes of birds are ancestral or derived ( Tiersch & Wachtel 1991)-that is, 'whether they have jettisoned their genomic baggage or whether it was never loaded in the first place' (Gregory 2002a,b)-is central to determining whether small genomes represent an adaptation to flight per se. New light has been recently shed on this issue by Organ et al (2007) who analysed the sizes of fossil osteocytes in dinosaurs and concluded that birds inherited already diminutive genomes from ancestral theropod dinosaurs (see also Ellegren 2007;Zimmer 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Bachmann et al 1972;Tiersch & Wachtel 1991). Available genome size estimates for roughly 200 species of birds reveal a range of only approximately twofold (approx.…”
Section: Introduction (A) Genome Size Diversity In Birdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to most birds, the A, vittata genome, is relatively small (1.59Gb), less than half the size of the human genome 5 . It is also highly invariable due to the recent population bottleneck 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Birds, reptiles and mammals display only a small variation in the DNA content within classes, with the genome size of birds being the most conserved (Tiersch and Wachtel, 1991). However, in amphibians, fish and insects there is a wide variation in C-values between species whose apparent complexity does not vary greatly.…”
mentioning
confidence: 99%